Climate policy and trade: Dynamics and the steady-state assumption in a multi-regional framework - Katrin Springer (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1999)
Most dynamic trade models assume steady state or balanced growth. This paper argues while this can be done in a single region model or a model without trade, the steady state assumption is problematic in a multi-regional setting with trade interactions. This paper shows the consequences of assuming a balanced growth path and discusses several problems which are connected to the calibration of recursive dynamic multi-regional trade models. Furthermore, it is demonstrated how different dynamic specifications of the base run path affect the results of a policy scenario by imposing the Kyoto Protocol. The simulations illustrate that a balanced growth path can not be maintained in a multi-regional trade model due to international trade spill-overs. It is shown that the model results and thus the assessment of climate policy options depend substantially on the dynamic specification.
Keywords: C68; D58; F43; O41; 330; Growth of open economies; Steady-state; Multi-regional dynamic CGE Model; International environmental problems; Klimaschutz; Wirkungsanalyse; Weltwirtschaft; Internationale Wirtschaftsbeziehungen; Außenwirtschaft; Allgemeines Gleichgewicht; Dynamisches Gleichgewicht; Mehr-Länder-Modell; Offene Volkswirtschaft; Steady-State-Wachstum; Theorie; Welt